Polyamide resin composition
The polyamide resin composition, with its specific blend of polyamide resin, olefinic ionomer, and impact-resistant material, addresses the challenges of blow moldability, low-temperature toughness, and blister resistance, achieving balanced performance in high-pressure gas tanks.
Patent Information
- Application Number
- JP2021553652
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-30
- Filing Date
- 2020-10-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-10-28
AI Technical Summary
Existing polyamide resin compositions used in blow molding face challenges in achieving balanced blow moldability, low-temperature toughness, and blister resistance, particularly in high-pressure gas tanks where dimensional stability and weld strength are critical.
A polyamide resin composition comprising 60-85% polyamide resin, 5-20% olefinic ionomer, and 5-20% impact-resistant material, with 20% or more of aliphatic copolymer polyamide, and optionally including a heat-resistant agent, to enhance mold transferability, burn resistance, and dimensional stability.
The composition concurrently exhibits excellent blow moldability, low-temperature toughness, and blister resistance, ensuring dimensional stability and preventing weld portion thinning in blow molded products, particularly in high-pressure gas tanks.
Smart Images

Figure 0007647563000002 
Figure 0007647563000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamide resin composition. [Background technology]
[0002] Polyamide resins have excellent mechanical properties, heat resistance, and chemical resistance, and are therefore used in a variety of applications as engineering plastics, and in a variety of molding methods. Among these, their use as blow molded products is also increasing. FCVs (fuel cell vehicles), which are expected to expand rapidly in the future, will require large blow molded products to hold fuel.
[0003] It is known that a polyamide resin composition in which a polyphenylene sulfide resin, an ethylene-based ionomer resin, and an olefin-based elastomer resin are added to a polyamide resin has excellent blow moldability, low-temperature toughness, and barrier properties (see, for example, Patent Document 1). Also, it is known that a polyamide resin composition made of 6-66 nylon copolymer and a modified polyolefin has excellent flexibility, gas barrier properties, and blow moldability (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-204675 A [Patent Document 2] Japanese Patent Application Publication No. 11-245927 Summary of the Invention [Problem to be solved by the invention]
[0005] It is known that blending an impact-resistant material such as an olefin-based elastomer resin with a polyamide resin improves the drawdown property and low-temperature toughness. However, on the other hand, there are problems such as poor mold transferability, burning, inner surface irregularities, dimensional stability, and blister resistance of blow molded products.
[0006] In these Patent Documents 1 and 2, it is confirmed that the thickness of the molded article is not biased as a whole as a measure of the dimensional stability of blow moldability. In blow molded articles, the thickness of the welded parts in particular tends to be thin, and when blow molded articles are used for high-pressure gas tanks and the like that require blister resistance and mechanical properties at extremely low temperatures, problems arise in that the welded parts crack or become brittle. Therefore, blow molded articles are required to have a uniform thickness as a whole, and also to have the thickness of the welded parts not be thinner than other parts.
[0007] Therefore, an object of the present invention is to simultaneously achieve low-temperature toughness, blow moldability (drawdown property, mold transferability of the blow molded product, suppression of burning, suppression of inner surface irregularities, and dimensional stability) and blister resistance in a blow molded product. [Means for solving the problem]
[0008] The present invention includes, for example, the following [1] to [7]. [1] A polyamide resin composition comprising 100% by mass of a polyamide resin (A) in an amount of 60 to 85% by mass, an olefin-based ionomer (B) in an amount of 5 to 20% by mass, and an impact-resistant material (C) in an amount of 5 to 20% by mass, A polyamide resin composition comprising 20% by mass or more of an aliphatic copolyamide (A-1) based on 100% by mass of the polyamide resin (A). [2] The polyamide resin composition according to [1], further comprising 0.1 to 3 mass % of a heat stabilizer (D). [3] The polyamide resin composition according to [1] or [2], wherein the aliphatic homopolyamide (A-3) is less than 75 mass% in 100 mass% of the polyamide resin (A). [4] The polyamide resin composition according to any one of [1] to [3], wherein the aliphatic copolyamide (A-1) comprises at least one selected from the group consisting of polyamide 6 / 66 and polyamide 6 / 66 / 12. [5] The polyamide resin composition according to any one of [1] to [4], wherein the aliphatic copolyamide (A-1) has a relative viscosity of 3.0 or more as measured in accordance with JIS K 6920. [6] The polyamide resin composition according to any one of [1] to [5], wherein the olefin ionomer (B) has an MFR of 2 g / 10 min or less, measured at 190° C. under a load of 2.16 kg in accordance with JIS K7210 (1999). [7] The polyamide resin composition according to any one of [1] to [6], wherein the impact-resistant material (C) has an MFR of 2 g / 10 min or less as measured at 190° C. under a load of 2.16 kg in accordance with ASTM D1238. [8] A blow molded product made from the polyamide resin composition of any one of [1] to [7]. [9] A molded article made of the polyamide resin composition of any one of [1] to [7], which is a molded article that comes into contact with high-pressure gas and has a shape selected from the group consisting of a tank, a tube, a hose, and a film. Effect of the Invention
[0009] The polyamide resin composition of the present invention can simultaneously achieve blow moldability (drawdown property, mold transferability of blow molded products, suppression of burning, suppression of surface irregularities, and dimensional stability), low temperature toughness, and blister resistance. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 shows a cylindrical 3-liter bottle which is a blow-molded product, where FIG. 1(a) is an overall longitudinal cross-sectional view, FIG. 1(b) is a top view of the bottom, and FIG. 1(c) is an enlarged view of the welded part at the bottom and its vicinity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention relates to a polyamide resin composition comprising, based on 100 mass% of the polyamide resin composition, 60 to 85 mass% of a polyamide resin (A), 5 to 20 mass% of an olefin-based ionomer (B), and 5 to 20 mass% of an impact-resistant material (C), and comprising, based on 100 mass% of the polyamide resin (A), 20 mass% or more of an aliphatic copolyamide (A-1).
[0012] (A) Polyamide resin The polyamide resin composition contains a polyamide resin (A). The polyamide resin (A) contained in the polyamide resin composition contains 20% by mass or more of aliphatic copolyamide (A-1) in 100% by mass of the polyamide resin (A), preferably 40% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and most preferably contains only aliphatic copolyamide (A-1). By containing the aliphatic copolyamide (A-1) in the above range, the molding temperature can be lowered, and the suppression of burning and dimensional stability of the blow molded product are excellent. The polyamide resin (A) may contain, in addition to the aliphatic copolyamide (A-1), at least one selected from the group consisting of aromatic copolyamide (A-2), aliphatic homopolyamide (A-3) and aromatic homopolyamide (A-4). Among these, aliphatic homopolyamide is preferred.
[0013] (A-1) Aliphatic copolyamide The aliphatic copolyamide (A-1) is a polyamide resin composed of two or more aliphatic structural units. The aliphatic copolyamide (A-1) is a copolymer of a monomer selected from the group consisting of a combination of a diamine and a dicarboxylic acid, lactam, and aminocarboxylic acid. Here, the combination of a diamine and a dicarboxylic acid is regarded as one type of monomer by combining one type of diamine and one type of dicarboxylic acid.
[0014] Examples of diamines include aliphatic diamines such as ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, and 2,2,4 / 2,4,4-trimethylhexamethylenediamine; Examples of the diamines include alicyclic diamines such as 1,3- / 1,4-cyclohexyldiamine, bis(4-aminocyclohexyl)methane, bis(4-aminocyclohexyl)propane, bis(3-methyl-4-aminocyclohexyl)methane, (3-methyl-4-aminocyclohexyl)propane, 1,3- / 1,4-bisaminomethylcyclohexane, 5-amino-2,2,4-trimethyl-1-cyclopentanemethylamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, bis(aminopropyl)piperazine, bis(aminoethyl)piperazine, and norbornanedimethyleneamine. Among these, from the viewpoint of polymerization productivity, at least one selected from the group consisting of aliphatic diamines is preferred, at least one selected from the group consisting of linear aliphatic diamines is more preferred, and hexamethylenediamine is even more preferred. These diamines may be used alone or in appropriate combination of two or more.
[0015] Examples of dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedionic acid, dodecanedionic acid, tridecanedionic acid, tetradecanedionic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and eicosanedioic acid; and alicyclic dicarboxylic acids such as 1,3- / 1,4-cyclohexanedicarboxylic acid, dicyclohexanemethane-4,4'-dicarboxylic acid, and norbornanedicarboxylic acid. These dicarboxylic acids may be used alone or in appropriate combination of two or more.
[0016] Examples of lactams include ε-caprolactam, enantholactam, undecane lactam, dodecane lactam, α-pyrrolidone, α-piperidone, laurolactam, etc. Among these, from the viewpoint of polymerization production, at least one selected from the group consisting of ε-caprolactam, undecane lactam, dodecane lactam, and laurolactam is preferred. These lactams may be used alone or in suitable combination of two or more. Examples of aminocarboxylic acids include 6-aminocaproic acid, 7-aminoheptanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid. Among these, from the viewpoint of polymerization production, at least one selected from the group consisting of 6-aminocaproic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid is preferred. These aminocarboxylic acids may be used alone or in appropriate combination of two or more.
[0017] Specific examples of the aliphatic copolymer polyamide (A-1) include caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 66), caprolactam / hexamethylenediaminoazelaic acid copolymer (polyamide 6 / 69), caprolactam / hexamethylenediaminosebacic acid copolymer (polyamide 6 / 610), caprolactam / hexamethylenediaminoundecanoic acid copolymer (polyamide 6 / 611), caprolactam / hexamethylenediaminododecanoic acid copolymer (polyamide 6 / 612), caprolactam / aminoundeca Examples of the aliphatic copolymer polyamides include caprolactam / laurolactam copolymer (polyamide 6 / 11), caprolactam / hexamethylenediaminoadipic acid / laurolactam copolymer (polyamide 6 / 12), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminosebacic acid copolymer (polyamide 6 / 66 / 610), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminododecanedicarboxylic acid copolymer (polyamide 6 / 66 / 612), etc. The aliphatic copolymer polyamide (A-1) may be used alone or in the form of a mixture of two or more kinds.
[0018] Among these, those with a low melting point are preferred. With a low melting point, the molding temperature can be lowered, which makes it possible to suppress burning and inner surface unevenness, and also improves drawdown properties. The melting point is preferably 240°C or less, more preferably 200°C or less, as measured by a differential scanning calorimeter (DSC) in accordance with ISO11357-3 under a nitrogen atmosphere at a temperature increase of 20°C / min.
[0019] Among these, from the viewpoint of productivity, at least one selected from the group consisting of polyamide 6 / 66, polyamide 6 / 12 and polyamide 6 / 66 / 12 is preferred, at least one selected from the group consisting of polyamide 6 / 66 and polyamide 6 / 66 / 12 is more preferred, and polyamide 6 / 66 is particularly preferred.
[0020] From the viewpoints of preventing scorching and drawdown properties, the proportion of polyamide 6 in the copolymer containing polyamide 6 is preferably 60 to 95%. These aliphatic copolyamides (A-1) can be used alone or in a mixture of two or more kinds. When used in a mixture of two or more kinds, it is preferable to use polyamide 6 / 66 as one of them from the viewpoints of blow moldability and blister resistance.
[0021] The production equipment for the aliphatic copolyamide (A-1) may be a known polyamide production equipment such as a batch reaction vessel, a single- or multi-vessel continuous reaction equipment, a tubular continuous reaction equipment, a kneading reaction extruder such as a single-screw kneading extruder or a twin-screw kneading extruder. The polymerization method may be a known method such as melt polymerization, solution polymerization or solid-phase polymerization, and may be polymerized by repeating normal pressure, reduced pressure and increased pressure operations. These polymerization methods may be used alone or in combination as appropriate.
[0022] From the viewpoint of moldability, the relative viscosity of the aliphatic copolyamide (A-1) is preferably 3.0 or more, more preferably 3.5 or more and 5.0 or less, as measured in accordance with JIS K 6920 by dissolving 1 g of the aliphatic copolyamide in 100 ml of 96% concentrated sulfuric acid at 25°C.
[0023] The terminal amino group concentration of the aliphatic copolyamide (A-1) is determined by dissolving it in a mixed solvent of phenol and methanol and performing neutralization titration. The terminal amino group concentration of the aliphatic copolyamide (A-1) is preferably 30 μmol / g or more, more preferably 30 μmol / g or more and 50 μmol / g or less. If the terminal amino group concentration is within the above range, the compatibility with the olefin ionomer (B) described later is good, which is preferable in terms of drawdown property, dimensional stability and blister resistance.
[0024] (A-2) Aromatic copolyamide Aromatic polyamide is an aromatic polyamide resin containing at least one aromatic monomer component, for example, a polyamide resin obtained by polycondensation of aliphatic dicarboxylic acid and aromatic diamine, aromatic dicarboxylic acid and aliphatic diamine, or aromatic dicarboxylic acid and aromatic diamine. Aromatic copolyamide (A-2) is a polyamide resin consisting of two or more kinds of structural units among the above aromatic polyamide resins. Here, a combination of diamine and dicarboxylic acid is regarded as one kind of monomer by a combination of one kind of diamine and one kind of dicarboxylic acid.
[0025] Examples of the aliphatic diamines and aliphatic dicarboxylic acids used as the raw materials include the same as those exemplified in the description of the aliphatic copolyamides, and also include those exemplified as the alicyclic diamines and alicyclic dicarboxylic acids. Examples of the aromatic diamine include metaxylylenediamine and paraxylylenediamine, and examples of the aromatic dicarboxylic acid include naphthalenedicarboxylic acid, terephthalic acid, isophthalic acid, and phthalic acid. These aromatic diamines and aromatic dicarboxylic acids may be used alone or in appropriate combination of two or more. The aromatic copolymerized polyamide resin may contain structural units derived from lactam or aminocarboxylic acid. The lactam or aminocarboxylic acid may be selected from the group consisting of the aliphatic copolymerization Examples of the raw material for the polyamide resin include the same as those exemplified above. These lactams and aminocarboxylic acids may be used alone or in combination of two or more.
[0026] Specific examples of the aromatic copolyamide (A-2) include: Polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer(Polyamide 66 / 6T), Polyhexamethylene terephthalamide / Polycaproamide Copolymer (Polyamide 6T / 6), Polyhexamethylene adipamide / Polyhexamethylene isophthalamide Copolymer (Polyamide 66 / 6I), Polyhexamethylene isophthalamide / Polycaproamide Copolymer (Polyamide 6I / 6), Polydodecamide / Polyhexamethylene terephthalamide Copolymer (Polyamide 12 / 6T), Polyhexamethylene adipamide / Polyhexamethylene terephthalamide / Polyhexamethylene isophthalamide Copolymer (Polyamide 66 / 6T / 6I), Polyhexamethylene adipamide / Polycaproamide / Polyhexamethylene isophthalamide Copolymer (Polyamide 66 / 6 / 6I), Polyhexamethylene terephthalamide / Examples of the aromatic copolymer polyamide (A-2) include polyhexamethylene isophthalamide copolymer (polyamide 6T / 6I), polyhexamethylene terephthalamide / poly(2-methylpentamethylene terephthalamide) copolymer (polyamide 6T / M5T), etc. The aromatic copolymer polyamide (A-2) may be used alone or in combination of two or more. Among these, polyamide 6T / 6I is preferred.
[0027] The production apparatus and polymerization method for the aromatic copolyamide (A-2) may be the same as those exemplified in the section for the aliphatic copolyamide (A-1).
[0028] The degree of polymerization of the aromatic copolyamide (A-2) in the present invention is not particularly limited, but the relative viscosity measured in 98% sulfuric acid at a concentration of 1% according to JIS K 6920 and at a resin temperature of 25°C of the aromatic copolyamide (A-2) is preferably 1.5 to 4.0, more preferably 1.8 to 3.0.
[0029] The terminal amino group concentration of aromatic copolymer polyamide (A-2) is determined by dissolving it in a mixed solvent of phenol and methanol and performing neutralization titration. The terminal amino group concentration of aromatic copolymer polyamide (A-2) is 2.00 x 10 -5 eq / g or more 6.00×10 -5 eq / g or less is preferred.
[0030] When the aromatic copolyamide (A-2) is contained in the polyamide resin (A), the content of the aromatic copolyamide (A-2) in 100% by mass of the polyamide resin (A) is preferably 1 to 30% by mass, more preferably 3 to 20% by mass, from the viewpoints of mechanical properties and moldability.
[0031] (A-3) Aliphatic homopolyamide The aliphatic homopolyamide (A-3) is a polyamide resin consisting of one kind of aliphatic structural unit. The aliphatic homopolyamide (A-3) may consist of at least one of one kind of lactam and an aminocarboxylic acid which is a hydrolyzate of the lactam, or may consist of a combination of one kind of diamine and one kind of dicarboxylic acid. Here, the combination of one kind of diamine and one kind of dicarboxylic acid is regarded as one kind of monomer.
[0032] Examples of lactams include the same as those exemplified as the raw materials for the aliphatic copolyamide (A-1). Among these, from the viewpoint of polymerization production, one selected from the group consisting of ε-caprolactam, undecane lactam, dodecane lactam and laurolactam is preferred. Examples of aminocarboxylic acids include those exemplified as raw materials for the aliphatic copolyamide (A-1). Among these, from the viewpoint of polymerization production, one selected from the group consisting of 6-aminocaproic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid is preferred.
[0033] Examples of diamines include the same as those exemplified as the raw materials for the aliphatic copolyamide (A-1). Among these, from the viewpoint of polymerization productivity, aliphatic diamines are preferred, and hexamethylenediamine is more preferred.
[0034] The dicarboxylic acid may be the same as those exemplified as the raw material of the aliphatic copolyamide (A-1). Among these, an aliphatic dicarboxylic acid is preferred, adipic acid, sebacic acid, and dodecanedioic acid are more preferred, and sebacic acid or dodecanedioic acid are even more preferred.
[0035] Specific examples of the aliphatic homopolyamide (A-3) include polycaprolactam (polyamide 6), polyenantholactam (polyamide 7), polyundecane lactam (polyamide 11), polylaurolactam (polyamide 12), polyhexamethylene adipamide (polyamide 66), polytetramethylene dodecamide (polyamide 412), polypentamethylene azelamide (polyamide 59), polypentamethylene sebacamide (polyamide 510), polypentamethylene dodecamide (polyamide 512), polyhexamethylene azelamide (polyamide 69), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecamide (polyamide 612), polynoname Examples of the polyamides include poly(ethylene adipamide) (polyamide 96), poly(nonamethylene azelamide) (polyamide 99), poly(nonamethylene sebacamide) (polyamide 910), poly(nonamethylene dodecamide) (polyamide 912), poly(decamethylene adipamide) (polyamide 106), poly(decamethylene azelamide) (polyamide 109), poly(decamethylene decamamide) (polyamide 1010), poly(decamethylene dodecamide) (polyamide 1012), poly(dodecamethylene adipamide) (polyamide 126), poly(dodecamethylene azelamide) (polyamide 129), poly(dodecamethylene sebacamide) (polyamide 1210), poly(dodecamethylene dodecamide) (polyamide 1212), and polyamide 122. The aliphatic homopolyamide (A-3) may be used alone or as a mixture of two or more kinds.
[0036] Among these, from the viewpoint of polymerization productivity, the aliphatic homopolyamide (A-3) is preferably at least one selected from the group consisting of polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, and polyamide 612, more preferably at least one selected from polyamide 6, polyamide 11, polyamide 12, polyamide 610, and polyamide 612, and further preferably polyamide 6.
[0037] The production apparatus and polymerization method for the aliphatic homopolyamide (A-3) may be the same as those exemplified in the section on the aliphatic copolyamide (A-1).
[0038] The relative viscosity of the aliphatic homopolyamide (A-3) is measured at 25°C in accordance with JIS K 6920 by dissolving 1g of the aliphatic homopolyamide in 100ml of 96% concentrated sulfuric acid. The relative viscosity of the aliphatic homopolyamide is preferably 2.7 or more, more preferably 2.7 or more and 5.0 or less. From the viewpoint of further improving the effects of the present invention, it is even more preferably 2.7 or more and less than 4.5. When it is 2.7 or more, the melt viscosity of the polyamide composition is not too low, so that the parison shape retention is particularly good during blow molding, and when it is 5.0 or less, the melt viscosity of the polyamide composition is not too high, so that a uniform wall thickness of the molten resin is obtained during blow molding.
[0039] The terminal amino group concentration of the aliphatic homopolyamide (A-3) is determined by dissolving it in a mixed solvent of phenol and methanol and performing neutralization titration. The terminal amino group concentration of the aliphatic homopolyamide (A-3) is preferably 30 μmol / g or more, more preferably 30 μmol / g or more and 50 μmol / g or less.
[0040] The content of the aliphatic homopolyamide (A-3) in 100% by mass of the polyamide resin (A) is preferably less than 75% by mass, more preferably less than 70% by mass, and particularly preferably less than 60% by mass, from the viewpoints of mechanical properties and blow moldability. When the aliphatic homopolyamide (A-3) is contained in the polyamide resin (A), the content is preferably 0.1% by mass or more.
[0041] (A-4) Aromatic homopolyamide The aromatic homopolyamide (A-4) is an aromatic polyamide resin consisting of one type of structural unit derived from an aromatic monomer component, for example, a polyamide resin obtained by polycondensation of aliphatic dicarboxylic acid and aromatic diamine, aromatic dicarboxylic acid and aliphatic diamine, or aromatic dicarboxylic acid and aromatic diamine as raw materials. Here, the combination of diamine and dicarboxylic acid is regarded as one type of monomer by the combination of one type of diamine and one type of dicarboxylic acid.
[0042] Examples of the aliphatic diamines and aliphatic dicarboxylic acids used as raw materials include the same as those exemplified for the aliphatic polyamides, and also include those exemplified as the alicyclic diamines and alicyclic dicarboxylic acids. Examples of the aromatic diamine include metaxylylenediamine and paraxylylenediamine, and examples of the aromatic dicarboxylic acid include naphthalenedicarboxylic acid, terephthalic acid, isophthalic acid, and phthalic acid.
[0043] Specific examples of the aromatic homopolyamide (A-4) include poly Nona Examples of the aromatic homopolyamides (A-4) include methylene terephthalamide (polyamide 9T), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polyxylylene adipamide (polyamide MXD6), etc. The aromatic homopolyamides (A-4) may be used alone or in combination of two or more.
[0044] The production apparatus and polymerization method for the aromatic homopolyamide (A-4) may be the same as those exemplified in the section on the aliphatic copolyamide (A-1).
[0045] The degree of polymerization of the aromatic homopolyamide resin (A-4) in the present invention is not particularly limited. HomoThe relative viscosity of the polyamide measured at a resin temperature of 25° C. is preferably from 1.5 to 4.0, and more preferably from 1.8 to 3.0.
[0046] When the aromatic homopolyamide (A-4) is contained in the polyamide resin (A), the content of the aromatic homopolyamide (A-4) in 100 mass% of the polyamide resin (A) is preferably 1 to 30 mass%, more preferably 3 to 20 mass%, from the viewpoints of mechanical properties and moldability.
[0047] The polyamide resin (A) has a relative viscosity of 2.7 or more, preferably 2.7 to 5.0, as measured at 25°C by dissolving 1g of the polyamide resin in 100ml of 96% concentrated sulfuric acid according to JIS K-6920. From the viewpoint of further improving the effects of the present invention, it is more preferably 2.7 to less than 4.5. When it is 2.7 or more, the melt viscosity of the polyamide composition is not too low, and therefore the parison shape is well maintained, particularly during blow molding. When it is 5.0 or less, the melt viscosity of the polyamide composition is not too high, and therefore a uniform wall thickness of the molten resin can be obtained during blow molding.
[0048] When the polyamide resin (A) contains two or more polyamide resins having different relative viscosities (for example, at least one aliphatic homopolyamide (A-3) and at least one aliphatic copolyamide (A-1)), the relative viscosity of the polyamide resin (A) is preferably measured as described above. However, when the relative viscosity of each polyamide resin and its mixing ratio are known, the relative viscosity of the polyamide resin (A) may be determined by adding up the values obtained by multiplying each relative viscosity by the mixing ratio.
[0049] From the viewpoint of reactivity with the impact resistant material (C), the terminal amino group concentration of the polyamide resin (A) is preferably in the range of 30 μmol / g or more, more preferably in the range of 30 μmol / g to 110 μmol / g, and even more preferably in the range of 30 μmol / g to 70 μmol / g, as the terminal amino group concentration obtained by dissolving in a mixed solvent of phenol and methanol and performing neutralization titration. If it is 30 μmol / g or more, the reactivity with the impact resistant material (C) is good, and sufficient melt viscosity and impact resistance can be obtained. If it is 110 μmol / g or less, the melt viscosity is not too high, and the moldability is good.
[0050] When the polyamide resin (A) contains two or more polyamide resins having different terminal amino group concentrations (for example, at least one aliphatic homopolyamide (A-3) and at least one aliphatic copolyamide (A-1)), the terminal amino group concentration in the polyamide resin (A) is preferably measured by the above-mentioned neutralization titration. However, when the terminal amino group concentration of each polyamide resin and its mixing ratio are known, the terminal amino group concentration of the polyamide resin (A) may be determined by adding up the values obtained by multiplying each terminal amino group concentration by the mixing ratio.
[0051] The polyamide resin (A) is contained in an amount of 60 to 85 mass%, preferably 70 to 85 mass%, more preferably 73 to 80 mass%, based on 100 mass% of the polyamide resin composition. When the content of the polyamide resin (A) is within the above range, the mechanical properties and heat resistance are good, and further, the low-temperature properties and blow moldability are good.
[0052] (B) Olefin-based ionomer The polyamide resin composition contains an olefin-based ionomer (B). The olefin-based ionomer refers to a copolymer of an olefin and an α,β-unsaturated carboxylic acid and / or an α,β-unsaturated carboxylic acid ester, neutralized with a metal or metal ion. When the olefin-based ionomer (B) is blended, the parison properties during blow molding are significantly improved, but the melt viscosity does not increase significantly, so that the productivity is improved. Examples of the resin of the olefin-based ionomer (B) include (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymers. These may be used alone or in combination of two or more. The (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymer is a polymer obtained by copolymerizing ethylene and / or propylene with an α,β-unsaturated carboxylic acid and / or an α,β-unsaturated carboxylic acid ester monomer. Examples of the α,β-unsaturated carboxylic acid monomer include acrylic acid and methacrylic acid. Examples of the α,β-unsaturated carboxylic acid ester monomer include methyl ester, ethyl ester, propyl ester, butyl ester, pentyl ester, hexyl ester, heptyl ester, octyl ester, nonyl ester, decyl ester, etc. of these α,β-unsaturated carboxylic acids. These may be used alone or in combination of two or more. Metals and metal ions used in ionomers include Na, K, Cu, Mg, Ca, Ba, Zn, Cd, Al, Fe, Co, and Ni, as well as ions thereof. These may be used alone or in combination of two or more, but it is preferable to use at least Zn (also referred to as "zinc" in this specification). Among these, ionomers of ethylene-methacrylic acid copolymers are preferred. Commercially available olefin-based ionomers include the Himilan (registered trademark) series manufactured by Dow Mitsui Polychemical Co., Ltd.
[0053] The olefin ionomer (B) preferably has a melting point of 75 to 100°C, more preferably 80 to 95°C, as measured by a differential scanning calorimeter (DSC) in accordance with ISO11357-3 under a nitrogen atmosphere at a temperature increase of 20°C / min. The olefin ionomer (B) has a density of 940 to 980 kg / m as measured according to JIS K7112. 3 is preferably 950 to 970 kg / m 3 It is more preferable that: Furthermore, the metal ions contained in the olefin ionomer (B) preferably contain at least zinc, and the amount of zinc element as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) is more preferably 3% or more. It is preferable for the melting point, density and zinc content to be within the above ranges from the viewpoints of compatibility with polyamide and wall thickness stability due to suppression of swelling during blow molding.
[0054] The MFR of the olefin ionomer (B) measured at 190° C. under a load of 2.16 kg in accordance with JIS K7210 (1999) is preferably 2 g / 10 min or less, more preferably 1 g / 10 min or less. The MFR of the olefin ionomer (B) within the above range is preferable from the viewpoint of drawdown property and dimensional stability.
[0055] The olefin ionomer (B) is contained in an amount of 5 to 20 mass%, preferably 8 to 17 mass%, and more preferably 10 to 15 mass%, based on 100 mass% of the polyamide resin composition. When the content of the olefin ionomer (B) is within the above range, low-temperature properties and parison properties in blow molding become good.
[0056] (C) Impact-resistant material The polyamide resin composition contains an impact resistant material (C). Examples of the impact resistant material include rubber-like polymers. The impact resistant material preferably has a flexural modulus of 500 MPa or less as measured in accordance with ASTM D-790. Note that the impact resistant material (C) does not include an olefin-based ionomer (B).
[0057] Specific examples of the impact resistant material (C) include (ethylene and / or propylene) / α-olefin copolymers, (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymers, etc. These can be used alone or in combination of two or more. A preferred example of the impact resistant material (C) is an ethylene / α-olefin copolymer.
[0058] The (ethylene and / or propylene) / α-olefin copolymer is a polymer obtained by copolymerizing ethylene and / or propylene with an α-olefin having 3 or more carbon atoms or 4 or more carbon atoms. Examples of the α-olefin having 3 or more carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene. These may be used alone or in combination of two or more.
[0059] The copolymer may also be one obtained by copolymerizing a polyene such as a non-conjugated diene. Examples of the non-conjugated diene include 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, 4,8-dimethyl-1,4,8-decatriene (DMDT), dicyclopentadiene, ... Examples of the aryl group include butyl ether, cyclohexadiene, cyclooctadiene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,5-norbornadiene, etc. These may be used alone or in combination of two or more.
[0060] The (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymer is a polymer obtained by copolymerizing ethylene and / or propylene with α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester monomers. Examples of the α,β-unsaturated carboxylic acid monomers include acrylic acid and methacrylic acid. Examples of the α,β-unsaturated carboxylic acid ester monomers include methyl esters, ethyl esters, propyl esters, butyl esters, pentyl esters, hexyl esters, heptyl esters, octyl esters, nonyl esters, decyl esters, etc. of these α,β-unsaturated carboxylic acids. These may be used alone or in combination of two or more.
[0061] The impact-resistant material (C) preferably contains a functional group having affinity for the polyamide resin (A) in its molecule. The (ethylene and / or propylene) / α-olefin copolymer can contain a functional group having affinity for the polyamide resin (A) in its molecule by being modified with a carboxylic acid and / or a derivative thereof, and / or an unsaturated carboxylic acid and / or a derivative thereof. The (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymer contains a carboxyl group and / or a carboxylate group, and therefore contains a functional group having affinity for the polyamide resin (A) in its molecule, and may further be modified with a carboxylic acid and / or a derivative thereof, and / or an unsaturated carboxylic acid and / or a derivative thereof.
[0062] Examples of the functional group having an affinity for the polyamide resin (A) include a carboxy group, an acid anhydride group, a carboxylate group, a metal salt of a carboxylate, a carboxylic acid imide group, a carboxylic acid amide group, and an epoxy group.
[0063] Examples of compounds containing these functional groups include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, mesaconic acid, citraconic acid, glutaconic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, endo-bicyclo-[2.2.1]-5-heptene-2,3-dicarboxylic acid, and metal salts of these carboxylic acids, monomethyl maleate, monomethyl itaconate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, methyl methacrylate, and methacrylic acid. Examples of the methacrylic acid include 2-ethylhexyl, hydroxyethyl methacrylate, aminoethyl methacrylate, dimethyl maleate, dimethyl itaconate, maleic anhydride, itaconic anhydride, citraconic anhydride, endobicyclo-[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, maleimide, N-ethylmaleimide, N-butylmaleimide, N-phenylmaleimide, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, glycidyl itaconate, and glycidyl citraconate. These may be used alone or in combination of two or more. Among these, maleic anhydride is preferred.
[0064] Methods for introducing these functional groups into a resin include (i) copolymerizing a copolymerizable monomer having a functional group during polymerization of the resin, (ii) introducing a functional group into the molecular chain or molecular end of the resin using a polymerization initiator, a chain transfer agent, etc., and (iii) grafting a compound having a functional group and a functional group capable of grafting (graft compound) onto the resin, etc. These introduction methods can be used alone or in appropriate combination.
[0065] Among these, the (ethylene and / or propylene) / α-olefin copolymer used as the impact-resistant material (C) is preferably a polymer acid-modified with an unsaturated carboxylic acid or its acid anhydride, etc., and the (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymer is preferably a polymer acid-modified with an unsaturated carboxylic acid or its acid anhydride, etc., in addition to the functional groups already present. When the impact resistant material (C) contains an acid anhydride group, the content of the acid anhydride group in the impact resistant material (C) is preferably more than 25 μmol / g and less than 100 μmol / g, and more preferably 35 μmol / g or more and 95 μmol / g or less. / g It is more preferable that the content is less than 25 μmol / g, and even more preferable that the content is 40 μmol / g or more and 90 μmol / g or less. If the content is more than 25 μmol / g, a composition with high melt viscosity can be obtained, and the target wall thickness can be obtained in blow molding. If the content is less than 100 μmol / g, the melt viscosity is not too high, and the load on the extruder can be reduced, allowing good molding processing. The content of acid anhydride groups in the impact-resistant material (C) is measured by neutralization titration with a 0.1N KOH ethanol solution using a sample solution prepared using toluene and ethanol and phenolphthalein as an indicator.
[0066] When two or more types of impact resistant materials having different acid anhydride group contents are used as the impact resistant material (C), the acid anhydride group content in the impact resistant material (C) is preferably measured by neutralization titration using a sample solution prepared using toluene and ethanol, phenolphthalein as an indicator, and a 0.1N KOH ethanol solution. However, when the acid anhydride group content of each impact resistant material and its mixing ratio are known, the acid anhydride group content of each impact resistant material may be multiplied by the mixing ratio and the total value calculated as the acid anhydride content of the impact resistant material (C), and the average value calculated as the acid anhydride content of the impact resistant material (C) may be used.
[0067] The impact-resistant material (C) preferably has an MFR of 2 g / 10 min or less, measured at a temperature of 190° C. and a load of 2.16 kg according to ASTM D1238. When the MFR is within the above range, the shape of the parison is prevented from becoming unstable during blow molding, and the thickness of the molded article tends to be more uniform. In addition, the drawdown of the parison is not too large, and good blow moldability tends to be obtained.
[0068] The impact-resistant material (C) is contained in an amount of 5 to 20 mass %, preferably 5 to 15 mass %, based on 100 mass % of the polyamide resin composition. When the content of the impact-resistant material (C) is within the above range, the suppression of burning, low-temperature physical properties, and uniformity of the wall thickness of the blow molded product are good.
[0069] The polyamide resin composition contains both the olefin ionomer (B) and the impact-resistant material (C), and thus achieves both resistance to burning and blistering, and is also excellent in dimensional stability.
[0070] (D) Heat-resistant agent The polyamide resin composition preferably contains a heat-resistant agent (D). The heat-resistant agent can be one that can improve the heat resistance of the polyamide resin, and organic or inorganic heat-resistant agents can be used depending on the purpose.
[0071] From the viewpoint of heat welding property and heat resistance property, it is more preferable that the polyamide resin composition contains at least one organic antioxidant as a heat resistance agent. By containing an organic antioxidant, it is possible to further improve heat welding property while maintaining normal heat aging property, physical properties, melt viscosity, etc., even if the interval time during blow molding is long. This is thought to be because, for example, the addition of an organic antioxidant suppresses gelation due to thermal deterioration of the impact resistance agent, thereby suppressing the nucleation action.
[0072] (Organic heat resistant agent) Examples of the organic antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants.
[0073] A preferred example of the phenol-based antioxidant is a hindered phenol-based antioxidant. In this specification, the hindered phenol refers to a compound having a substituent at the ortho-position (hereinafter also referred to as "o-position") of the phenolic hydroxyl group. The substituent at the o-position is not particularly limited, but includes an alkyl group, an alkoxy group, an amino group, a halogen, and the like. Among these, an alkyl group such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a sec-butyl group, an i-butyl group, a t-butyl group, and the like is preferred, a bulky i-propyl group, a sec-butyl group, an i-butyl group, a t-butyl group, and the like is more preferred, and a t-butyl group is the most preferred. In addition, it is preferred that both of the two o-positions relative to the phenolic hydroxyl group have a substituent. Specific examples of the hindered phenol having a t-butyl group at the o-position include N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide, pentaerythritol-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate, ethylenebis(oxyethylene)bis[3-(5-t-butyl-4-hydroxy-m-tolyl)propionate], and 3,9-bis[2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane. These may be used alone or in combination of two or more. Commercially available products of these heat-resistant additives include "Irganox (registered trademark) 1010" (BASF) and "Sumilizer (registered trademark) GA-80" (Sumitomo Chemical).
[0074] As the phosphorus-based antioxidant, a phosphite compound of a hindered phenol or a hypophosphite compound of a hindered phenol is preferred, a phosphite compound of a hindered phenol having a t-butyl group at the o-position or a hypophosphite compound of a hindered phenol having a t-butyl group at the o-position is more preferred, and a phosphite compound of a hindered phenol having a t-butyl group at the o-position is even more preferred. Specific examples of the phosphite compound of a hindered phenol having a t-butyl group at the o-position include tris(2,4-di-t-butylphenyl)phosphite and bis(2,6-di-t-butyl-4-methylphenyl)pentaerthritol diphosphite. Specific examples of hypophosphite compounds of hindered phenols having a t-butyl group at the o-position include reaction products of biphenyl, phosphorus trichloride, and 2,4-di-t-butylphenol, mainly composed of p,p,p',p'-tetrakis(2,4-di-t-butylphenoxy)-4,4'-biphenyldiphosphine. Commercially available products of these heat-resistant agents include "Irgafos (registered trademark) 168" (BASF) and "Hostanox (registered trademark) P-EPQ (registered trademark)" (Clariant Chemicals). These may be used alone or in combination of two or more. Examples of sulfur-based antioxidants include distearyl-3,3-thiodipropionate, pentaerythrityl tetrakis (3-lauryl thiopropionate), and didodecyl (3,3'-thiodipropionate). These may be used alone or in combination of two or more. These organic antioxidants may be used alone or in combination of two or more.
[0075] (Inorganic heat resistant agent) The heat-resistant agent may be an inorganic heat-resistant agent, such as a copper compound or a potassium halide. Examples of the copper compound include copper (I) iodide, copper (I) bromide, copper (II) bromide, and copper acetate. In terms of heat resistance and inhibition of metal corrosion, copper (I) iodide is preferred. Examples of the potassium halide include potassium iodide, potassium bromide, and potassium chloride. In terms of heat resistance and inhibition of metal corrosion, potassium iodide and / or potassium bromide are preferred. These may be used alone or in combination of two or more.
[0076] In addition, melamine, Zo It is more effective to use a nitrogen-containing compound such as guanamine, dimethylol urea or cyanuric acid in combination. From the viewpoint of thermal weldability, the polyamide resin composition preferably contains at least one type of phenol-based antioxidant, more preferably contains at least one type of phenol-based antioxidant and at least one type of phosphorus-based antioxidant, further preferably contains a hindered phenol having a t-butyl group at the o-position and a phosphite compound of a hindered phenol having a t-butyl group at the o-position or a hypophosphite compound of a hindered phenol having a t-butyl group at the o-position, and particularly preferably contains a hindered phenol having a t-butyl group at the o-position and a phosphite compound of a hindered phenol having a t-butyl group at the o-position.
[0077] The heat-resistant agent (D) is preferably contained in an amount of 0.1 to 3 mass%, more preferably 0.5 to 2 mass%, based on 100 mass% of the polyamide resin composition. When the content of the heat-resistant agent (D) is within the above range, it is possible to suppress scorching in the appearance of the molded article, uneven thickness on the inner surface, and yellowing of the entire molded article, thereby improving the appearance.
[0078] (E) Additives The polyamide resin composition may contain, as optional components, appropriate functionalizing agents such as dyes, pigments, fibrous reinforcements, particulate reinforcements, plasticizers, antioxidants (excluding component (D)), foaming agents, weathering agents, crystal nucleating agents, crystallization accelerators, release agents, lubricants, antistatic agents, flame retardants, flame retardant assistants, and colorants, depending on the purpose, etc. In order to improve the effects of the present invention, the polyamide resin composition preferably contains an antioxidant. The optional additive (E) is contained in an amount of preferably 0.01 to 1 mass %, more preferably 0.05 to 0.5 mass %, based on 100 mass % of the polyamide resin composition.
[0079] The polyamide resin composition may contain a resin other than the polyamide resin (A), the olefin-based ionomer (B), and the impact-resistant material (C). From the viewpoint of suppressing burning, the resin other than the polyamide resin (A), the olefin-based ionomer (B), and the impact-resistant material (C) is preferably contained in an amount of 2 mass% or less, more preferably less than 0.1 mass%, and even more preferably zero, based on 100 mass% of the polyamide resin composition.
[0080] [Method of producing polyamide resin composition] The method for producing the polyamide resin composition is not particularly limited, and for example, the following method can be applied. For mixing the polyamide resin (A), the olefin-based ionomer (B), the impact resistant material (C), the optional heat-resistant agent (D), and other optional components, a commonly known melt kneader such as a single-screw or twin-screw extruder, a Banbury mixer, a kneader, or a mixing roll may be used. For example, any of the following methods may be used: a method in which all raw materials are blended using a twin-screw extruder, and then melt-kneaded; a method in which some raw materials are blended, then melt-kneaded, and then the remaining raw materials are blended and melt-kneaded; or a method in which some raw materials are blended, and then the remaining raw materials are mixed using a side feeder during melt kneading.
[0081] [Uses of polyamide resin composition] The polyamide resin composition has a parison retention ability despite its low melt viscosity, and even if it is retained during molding, the surface appearance of the molded article is excellent, so that it can be suitably used for producing blow molded products by blow molding.Furthermore, it can be suitably used for producing extrusion molded products by extrusion molding, injection molded products by injection molding, and rotational molded products by rotational molding.
[0082] The method for producing a blow molded product from a polyamide resin composition by blow molding is not particularly limited, and a known method can be used. In general, a parison is formed using a normal blow molding machine, and then blow molding is performed. The resin temperature during parison formation is preferably in the range of 10°C to 70°C higher than the melting point of the polyamide resin composition.
[0083] A blow molded article obtained by blow molding the polyamide resin composition has reduced deviation in thickness and is excellent in dimensional stability. As shown in FIG. 1, in a blow molded article made of a polyamide resin composition, the standard deviation of the thickness at each of five locations, i.e., shoulder portion 1, R portion 2, body portion 3, vicinity of welded portion 4, and welded portion 5, is preferably 1.00 or less, more preferably 0.90 or less, and even more preferably 0.80 or less.
[0084] In particular, in a blow molded article obtained by blow molding the polyamide resin composition, the wall thickness of the welded portion is prevented from becoming thin. In the blow molded product made of a polyamide resin composition, the value obtained by dividing the thickness of the welded portion 5 by the average thickness of the five locations, i.e., the shoulder portion 1, the R portion 2, the body portion 3, the vicinity of the welded portion 4, and the welded portion 5 (thickness of the welded portion / average thickness) is preferably 0.50 or more, more preferably 0.55 or more, and even more preferably 0.60 or more.
[0085] The method for producing an extrusion molded article from the polyamide resin composition by extrusion molding is not particularly limited, and any known method can be used. It is also possible to obtain a multi-layer structure by co-extrusion with a polyolefin such as polyethylene or other thermoplastic resin, followed by blow molding. In this case, it is also possible to provide an adhesive layer between the polyamide resin composition layer and the other thermoplastic resin layer such as polyolefin. In the case of a multi-layer structure, the polyamide resin composition of the present invention can be used for either the outer layer or the inner layer.
[0086] The method for producing an injection-molded article from the polyamide resin composition by injection molding is not particularly limited, and any known method can be used, for example, a method conforming to ISO294-1.
[0087] The method for producing a rotational molded article from the polyamide resin composition by rotational molding is not particularly limited, and a known method can be used. For example, the method described in International Publication WO 2019 / 054109 can be referred to.
[0088] Examples of the blow molded products by blow molding, extrusion molded products by extrusion molding, injection molded products by injection molding, and rotational molded products by rotational molding are not particularly limited, but include automobile parts such as spoilers, air intake ducts, intake manifolds, resonators, fuel tanks, gas tanks, hydraulic oil tanks, fuel filler tubes, fuel delivery pipes, and other various hoses, tubes, and tanks, machine parts such as electric tool housings and pipes, as well as various applications such as electric and electronic parts, household and office supplies, building material-related parts, and furniture parts. Among these, molded products of the polyamide resin composition of the present invention are excellent in blow moldability that can be used for large molded products, and also have excellent impact resistance, and therefore can be more preferably used for large tanks, particularly high-pressure gas tanks.
[0089] In addition, since the polyamide resin composition has excellent gas barrier properties, it is suitable for use in molded products that come into contact with high-pressure gas, such as tanks, tubes, hoses, films, etc. The type of gas is not particularly limited and examples thereof include hydrogen, nitrogen, oxygen, helium, methane, butane, propane, etc., with gases having low polarity being preferred, and hydrogen, nitrogen, and methane being particularly preferred. EXAMPLES
[0090] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The methods for evaluating the physical properties of the resins and molded articles used in the examples and comparative examples are shown below.
[0091] (Blow moldability) The blow moldability was evaluated according to (1) to (5). The blow moldability was confirmed using a blow molding machine DA-50 with accumulation head manufactured by Placo Corporation. The measurement conditions were a cylinder temperature of 240°C, a screw rotation speed of 40 rpm, a die aperture of 50 mm, a cylindrical 3-liter bottle mold, and a mold temperature of 60°C. Molded products were obtained. The obtained molded products were used for evaluations (2) to (5). Evaluation (1) was also performed under these conditions.
[0092] (1) Drawdown A parison was extruded at a constant thickness for 1 m, and the amount of sagging was measured after 2 seconds to evaluate the drawdown property. The smaller the amount of sagging, the better the drawdown property. Specifically, a sagging amount of 15 cm or less indicates excellent drawdown property.
[0093] (2) Internal burns The internal surface burn of the blow molded product was judged by visual inspection according to the following criteria. Products with a score of 2 or 3 were considered to pass. 3: Almost no burning is observed on the entire molded product, and the surface is glossy. 2: There is some burning in the thicker parts, but the surface is glossy. 1: The molded product has burns and the surface has no gloss.
[0094] (3) Inner surface unevenness To check the thickness uniformity, the unevenness of the inner surface was visually observed and evaluated according to the following criteria: The less unevenness there was, the better the thickness uniformity. ◯: The surface condition is the same as the outer surface, and is uniform with no significant irregularities. ×: Significant irregularities different from the outer surface are observed.
[0095] (4) Outer surface mold transferability The transferability of the mold on the outer surface of the blow molded product was judged by visual inspection according to the following criteria. ◯: The transferability of the mold is good. ×: The transferability of the mold is poor.
[0096] (5) Dimensional stability The thickness of the blow molded product was measured with a vernier caliper at five locations, namely shoulder 1, R portion 2, body 3, vicinity of welded portion 4, and welded portion 5, as shown in Figure 1, and the standard deviation was calculated. If the standard deviation is 1.00 or less, there is little difference in thickness between locations in the molded product, and the dimensional stability is good. Based on the measured values, the thickness of the welded part 5 was divided by the average thickness of the five locations, namely, the shoulder part 1, the R part 2, the body part 3, the vicinity of the welded part 4, and the welded part 5, to determine the value (thickness of the welded part / average thickness). If this value is small, the welded part will be thinner than the whole. Therefore, if this value is 0.50 or more, it is possible to prevent only the welded part from being significantly thinner.
[0097] (6) Low temperature toughness Test specimens were prepared according to ISO294-1 using an injection molding machine SE100D-C160S manufactured by Sumitomo Heavy Industries, Ltd. The obtained test specimens were used to obtain data on mechanical properties. (6-1) Nominal tensile strain at break at -60℃ It was measured at -60℃ using an Instron tensile testing machine, model 5567, in accordance with ISO527-2 / 1A / 50. If the nominal tensile strain at break at -60℃ is 20% or more, the low-temperature toughness is good. (6-2) Charpy impact strength at -40℃ In accordance with ISO179-1 / 1eA, edgewise impact tests were conducted at -40°C using a 4mm thick test piece with an A notch using a Yasuda Seiki Charpy impact tester No. 258-PC (n=10). The Charpy impact strength at -40°C was 20kJ / m 2If it is equal to or greater than this, the low temperature toughness is good.
[0098] (7) Blister resistance Test specimens were prepared according to ISO294-1 using an injection molding machine SE100D-C160S manufactured by Sumitomo Heavy Industries, Ltd. The obtained test specimens were used to obtain data on mechanical properties. High pressure hydrogen gas at 85°C was charged into the autoclave over 30 minutes until the pressure increased from 2 MPa to 87.5 MPa, and the test specimen was placed inside. After holding the autoclave for 10 minutes, the pressure was reduced to 2 MPa at a rate of 0.5 minutes. This cycle was repeated four times before the specimen was removed. The test specimen was visually inspected for any abnormalities such as blisters. ○: No blisters on the surface of the test piece ×: Blisters appear on the surface of the test piece
[0099] (8) Overall rating The physical property evaluations (1) to (7) were comprehensively evaluated according to the following criteria. 〇: Drawdown: 15cm or less after 2 seconds. Regarding internal burn, the rating according to the above criteria is 2 or 3, Regarding the inner surface unevenness, the evaluation based on the above criteria was ◯, Regarding the outer surface mold transferability, the evaluation based on the above criteria was ◯, Dimensional stability: standard deviation is 1.00 or less and the thickness of the welded part / average thickness is 0.5 or more. Tensile break strain at -60°C is 20% or more. Charpy impact strength at -40℃ is 20kJ / m 2 That's all, Regarding blister resistance, the evaluation according to the above criteria was ◯. Satisfy all of the above. ×: Drawdown amount after 2 seconds is 15 cm or less. Regarding internal burn, the rating according to the above criteria is 2 or 3, Regarding the inner surface unevenness, the evaluation based on the above criteria was ◯, Regarding the outer surface mold transferability, the evaluation based on the above criteria was ◯, Dimensional stability: standard deviation is 1.00 or less and the thickness of the welded part / average thickness is 0.5 or more. Tensile break strain at -60°C is 20% or more. Charpy impact strength at -40℃ is 20kJ / m 2 That's all, Regarding blister resistance, the evaluation according to the above criteria was ◯. Does not meet one or more of the above.
[0100] [Examples 1 to 9, Comparative Examples 1 to 5] The components shown in Table 1 were melt-kneaded in a twin-screw kneader TEX44HCT with a cylinder diameter of 44 mm L / D 35 at a cylinder temperature of 250° C., a screw rotation of 160 rpm, and a discharge rate of 50 kg / hr to prepare the desired polyamide resin composition pellets. The units of compositions in the tables are mass %, with the entire resin composition being 100 mass %. The pellets obtained were used for the molded articles and test pieces used in the above-mentioned physical property evaluations, and the results are shown in Table 1.
[0101] [Table 1]
[0102] From the examples, it is clear that the polyamide resin composition of the present invention satisfies both low-temperature toughness, blow moldability such as mold transferability of blow-molded products, suppression of burning, suppression of surface unevenness, drawdown property and dimensional stability, and blister resistance. Comparing the Examples with Comparative Examples 1 and 4, it can be seen that when the amount of aliphatic copolyamide in the polyamide is less than 20 mass %, the dimensional stability is poor and the mold transferability may also be poor. In terms of dimensional stability, the thickness of the welded part is particularly thin. Comparing the Examples and Comparative Example 2, when the polyamide resin composition does not contain an impact resistant material and contains more than 20 mass % of ionomer, the dimensional stability and blister resistance are poor. Comparing the Examples and Comparative Example 3, when the polyamide resin composition does not contain an ionomer and contains more than 20 mass % of an impact-resistant material, the inner surface of the molded article is not inhibited from burning, and the dimensional stability is poor. Comparing the Examples and Comparative Example 5, if the polyamide resin composition does not contain an impact resistant material and an ionomer, blow molding itself is impossible and the low-temperature toughness is also poor.
[0103] The abbreviations in the table are as follows. (Polyamide resin) PA6: Polyamide 6, Relative viscosity: 4.08 PA6 / 66 (1): Polyamide 6 / 66, relative viscosity: 4.05, PA6 80mol%, PA66 20mol% PA6 / 66 (2): Polyamide 6 / 66, relative viscosity: 4.05, PA6 85mol%, PA66 15mol% PA6 / 66 / 12: Polyamide 6 / 66 / 12, relative viscosity: 4.05, PA6 80mol%, PA66 10mol%, PA12 10mol% The relative viscosity of the polyamide resin is a value measured at 25° C. in accordance with JIS K 6920 by dissolving 1 g of the polyamide resin in 100 ml of 96% concentrated sulfuric acid.
[0104] (Olefin-based ionomer) Zn-EM Ionomer: Density 960kg / m 3 Melting point: 88°C; MFR: 0.9g / 10min measured at 190°C and a load of 2.16kg according to JIS K7210 (1999); zinc content: 3.4% by mass; ethylene-methacrylic acid copolymer; metal ion: zinc; product name: Himilan (registered trademark) 1706, manufactured by Dow Mitsui Polychemicals Co., Ltd.
[0105] (Shockproof material) MAH-EBR: Maleic anhydride modified ethylene-butene copolymer, product name "Tafmer (registered trademark) MH5020" manufactured by Mitsui Chemicals, Inc., MFR measured at 190°C and a load of 2.16 kg in accordance with ASTM D1238: 0.6 g / 10 min.
[0106] (Heat resistance agent) Phenol-based 1: Phenol-based antioxidant (3,9-bis[2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane), product name "Sumilizer (registered trademark) GA-80" manufactured by Sumitomo Chemical Co., Ltd. Phenol-based 2: Phenol-based antioxidant (pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]), product name "Irganox (registered trademark) 1010" manufactured by BASF Phosphorus-based 1: Phosphorus-based antioxidant (a reaction product of biphenyl, phosphorus trichloride, and 2,4-di-t-butylphenol, mainly composed of p,p,p',p'-tetrakis(2,4-di-t-butylphenoxy)-4,4' (or 3',4)-biphenyldiphosphine), product name "Hostanox (registered trademark) P-EPQ (registered trademark)", manufactured by Clariant Chemicals Phosphorus-based 2: Phosphorus-based antioxidant (tris(2,4-di-t-butylphenyl)phosphite), product name "Irgafos (registered trademark) 168" manufactured by BASF [Explanation of symbols]
[0107] 1 Shoulder 2 R section 3. Torso 4. Near the welded part 5 Welded area
Claims
1. The polyamide resin composition contains 73 to 85 mass% of a polyamide resin (A), 5 to 20 mass% of an olefin ionomer (B), and 5 to 20 mass% of an impact resistant material (C) based on 100 mass% of the polyamide resin composition, The polyamide resin (A) contains 40% by mass or more of an aliphatic copolyamide (A-1) in 100% by mass of the polyamide resin (A), The aliphatic copolymer polyamide (A-1) is selected from the group consisting of caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 66), caprolactam / hexamethylenediaminoazelaic acid copolymer (polyamide 6 / 69), caprolactam / hexamethylenediaminosebacic acid copolymer (polyamide 6 / 610), caprolactam / hexamethylenediaminoundecanoic acid copolymer (polyamide 6 / 611), caprolactam / hexamethylenediaminododecanoic acid copolymer (polyamide 6 / 612), caprolactam / aminoundecanoic acid copolymer (polyamide 6 / 613), caprolactam / hexamethylenediaminododecanoic acid copolymer (polyamide 6 / 614), caprolactam / aminoundecanoic acid copolymer (polyamide 6 / 615), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 616), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 617), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 618), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 619), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 620), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 621), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 622), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 623), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 624), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 625), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 / 626), caprolactam / hexamethylenediaminoadipic acid copolymer (polyamide 6 at least one selected from the group consisting of caprolactam / laurolactam copolymer (polyamide 6 / 11), caprolactam / laurolactam copolymer (polyamide 6 / 12), caprolactam / hexamethylenediaminoadipic acid / laurolactam copolymer (polyamide 6 / 66 / 12), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminosebacic acid copolymer (polyamide 6 / 66 / 610), and caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminododecanedicarboxylic acid copolymer (polyamide 6 / 66 / 612); The impact-resistant material (C) is at least one selected from the group consisting of (ethylene and / or propylene) / α-olefin copolymers modified with carboxylic acid and / or derivatives thereof and / or unsaturated carboxylic acid and / or derivatives thereof, and (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or α,β-unsaturated carboxylic acid ester) copolymers which may be modified with carboxylic acid and / or derivatives thereof and / or unsaturated carboxylic acid and / or derivatives thereof. Polyamide resin composition.
2. The polyamide resin composition according to claim 1, further comprising 0.1 to 3 mass % of a heat-resistant agent (D).
3. 3. The polyamide resin composition according to claim 1, wherein the aliphatic homopolyamide (A-3) is less than 60% by mass in 100% by mass of the polyamide resin (A).
4. The polyamide resin composition according to any one of claims 1 to 3, wherein the aliphatic copolyamide (A-1) comprises at least one selected from the group consisting of polyamide 6 / 66 and polyamide 6 / 66 / 12.
5. A polyamide resin composition described in any one of claims 1 to 4, wherein the olefin ionomer (B) is a copolymer of an olefin and an α,β-unsaturated carboxylic acid and / or an α,β-unsaturated carboxylic acid ester neutralized with a metal or a metal ion.
6. The polyamide resin composition according to any one of claims 1 to 5, wherein the aliphatic copolyamide (A-1) has a relative viscosity of 3.0 or more as measured in accordance with JIS K 6920.
7. The polyamide resin composition according to any one of claims 1 to 6, wherein the olefin ionomer (B) has an MFR of 2 g / 10 min or less as measured at 190°C under a load of 2.16 kg in accordance with JIS K7210 (1999).
8. The polyamide resin composition according to any one of claims 1 to 7, wherein the impact-resistant material (C) has an MFR of 2 g / 10 min or less as measured at 190°C under a load of 2.16 kg in accordance with ASTM D1238.
9. A blow molded product of the polyamide resin composition according to any one of claims 1 to 8.
10. A molded article of the polyamide resin composition according to any one of claims 1 to 8, which is a molded article that comes into contact with high-pressure gas and has a shape selected from the group consisting of a tank, a tube, a hose and a film.
Citation Information
Patent Citations
Hollow molded article
JP1999245927A
Composition for blow-molding
JP2007204674A
Polyamide resin composition for blow molding
JP2007204675A
Resin composition and multilayer structure using the same
JP2012092290A
Polyamide resin composition and resin metal complex
JP2013249363A